師資培育國際化──國際文憑教師（IBEC）學程中的師資生特質與想法 Globalization of Teacher Education Program: Characteristics and Voices of Student Teachers in IBEC Program - 葉怡芬 Yi-Fen Yeh; 劉美慧 Mei-Hui Liu (National Taiwan Normal University, 2020)
國際文憑教育為世界認可的國際教育系統，其特色包含結構性的課程架構、與時俱進的教與學理論及實務、學校品質保證機制、教師專業發展等。有鑑於十二年國民基本教育對於高品質教師的需求，但同時又面臨少子化對教師缺額的縮減，國立臺灣師範大學就其多年於師資培育的專業再發展國際文憑教師證照學程，並於 2018 年完成官方認證且於同年開始招生。為瞭解師資生對於國際文憑教師證照學程的看法並進而選擇修習者的特質，本研究以兩份自陳問卷，包含探討師資生教師核心能力、修習教育專業課程後的態度與信念，以及對於 國際教師學分學程看法的問卷，調查該校選擇修習國際文憑教師證照學程（n＝51）與未選擇修習的師資生（n＝120）；並藉由訪問 5 位國際文憑教育者，瞭解師資生對於成為國際文憑教師想法是否符合國際文憑學校師資需求。結果顯示選擇修習國際文憑教師證照學程的師資生在以教師為志業的內在動機及核心能力上（特別是熱愛教育與反省增能）顯著高於未申請者。本研究的目的在於藉由分析師資生對於修習國際文憑教師證照學程的想法與特質，探討師資職前教育課程的可能發展方向，包括培養明日教師的國際思維與雙語教學能力，以提升臺灣教育的水準。 International Baccalaureate (IB) is a world-recognized international education system that has structured curriculum frameworks, up-to-date teaching and learning theories and practices, a school quality assurance mechanism, and a teacher professional development system, among other notable features. Considering the demands of high-quality teachers from the 12-year educational reform and in light of the threat of reductions in teaching jobs, National Taiwan Normal University (NTNU), based on its long-term endeavors in promoting teacher education, implemented the IB Educator Certificate (IBEC) Program, which was officially recognized and launched in 2018. To better understand the characteristics of contemporary student teachers, this study surveyed cohorts of IBEC program applicants (n = 51) and individuals who did not apply (n = 120) through two self-reported questionnaires. Five experienced IB educators were also interviewed to acquire information on the type of teachers IB schools were expecting to hire. Results showed that the cohort that applied to the IBEC Program had significantly higher intrinsic motivation for becoming teachers, education passion, and reflective empowerment, which explained their willingness to invest time into taking the IBEC Program. After updated information was collected from student teachers on teacher education programs, this study explored possible next steps for teacher education, such as inclusion of international education and bilingual education elements to meet the needs of the upcoming generation.